PEMETAAN BIBLIOMETRIK: PENGGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) PADA RENTANG WAKTU 2011-2023 DALAM DUNIA PENDIDIKAN - Raihanzaki, Raka Gading; Yuadi, Imam (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
Artificial Intelligence technology is artificial intelligence which is then associated with the ability of machines or computers to do things that humans do. Artificial Intelligence originally started in 1942 when the American science fiction writer Isaac Asimov then included AI in his book entitled Runaround which then told about robots. Then, in 1956 MarvinMinsky and John McCarthy began conducting research on artificial intelligence. Artificial Intelligence technology has become increasingly popular among the wider community, in all circles, including in the world of education. One of the products from AI which is quite popular at the moment is GPT chat which is often used in the world of education. This is because Artificial Intelligence technology makes it very easy to do work or assignments. This article will then examine using bibliometric analysis the trends in the use of Artificial Intelligence technology in the world of education. This article analyzes using the bibliometric analysis method using a database from Scopus with a research range from 2011 to 2023, with the keywords artificial intelligence, impact, and education, which then produces 1565 articles. These articles were analyzed using bibliometric methods with biblioshiny. The aim of this article is to analyze trends in the use of artificial intelligence technology in the world of education based on bibliometric analysis by observing the number of publications on this topic from year to year. It was found that from year to year research on the use of artificial intelligence in the world of education, the graph continues to increase and shows a percentage of 43.71% for the development of publications from year to year. This article is divided into several parts (1) introduction which explains each research component starting from scopus bibliometrics and biblioshiny as well as the topics studied; (2) research methods carried out using bibliometric analysis; (3) results and discussion of the bibliometric analysis; and (4) conclusions.